RANCANG BANGUN RANGKA MESIN PEMARUT KELAPA MENGGUNAKAN MESIN MOTOR JUPITER Z1 113 CC - Fiqri, Moch Qori Rizalul; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2024)
Technological innovation in the field of machinery is used to make human work easier, as well as reviewing the needs of the industrial market which continues to develop with the times. Therefore, the purpose of this writing is to try an innovation in the field of machinery. The experimental methodology for making the frame for the coconut grater machine, as well as the design of the frame for the coconut grater machine using the Jupiter z1 motorbike engine follows the shape of the machine and there are 2 frames with different shapes because the frames have different functions. One frame is used to store the machine, while the other frame is used to store the grating knife.